1993
DOI: 10.1002/1097-0142(19930301)71:5<1848::aid-cncr2820710522>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Use of pilocarpine during head and neck radiation therapy to reduce xerostomia and salivary dysfunction

Abstract: Background. Salivary gland hypofunction commonly develops during radiation therapy to the head and neck region. This study evaluated whether the sialogogue pilocarpine given during radiation therapy may reduce the severity of xerostomia and salivary dysfunction. Methods. Nine patients requiring head, neck, or mantle radiation therapy participated in this double‐blind, placebo‐controlled trial. The patients took either 5 mg of pilocarpine or placebo four times daily for 3 months, beginning the day before radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 11 publications
0
45
0
4
Order By: Relevance
“…A single clinical trial on a further protection of radiogenic sialadenitis and mucositis by coumarin/troxerutine was also reported by Grotz et al (10). Among the so-called preemptive drugs, pilocarpin has gained ground, not only in experimental studies (11) but in clinical trials as well (12,13). Postulating the hypothesis of basolateral membrane damage as an initial target site of radiation, Stephens et al (14) suggested a further prophylactic approach, which has been proven to reduce this damage in cell culture, namely the membrane stabilization agent lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…A single clinical trial on a further protection of radiogenic sialadenitis and mucositis by coumarin/troxerutine was also reported by Grotz et al (10). Among the so-called preemptive drugs, pilocarpin has gained ground, not only in experimental studies (11) but in clinical trials as well (12,13). Postulating the hypothesis of basolateral membrane damage as an initial target site of radiation, Stephens et al (14) suggested a further prophylactic approach, which has been proven to reduce this damage in cell culture, namely the membrane stabilization agent lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Valdez et al [28] was the first randomized double blind clinical trial that evaluated the use of pilocarpine during the course of RT. A total of 9 patients with HNC took either pilocarpine or placebo four times daily for 3 months, beginning the day before RT.…”
Section: Pilocarpine Hydrochloridementioning
confidence: 89%
“…The prophylactic use of systemic sialogogues for radiationinduced xerostomia is widely reported in the literature [28][29][30][31][32][33][34][35][36]. These drugs are defined as systemic stimulants of salivary gland function by acting directly on the parasympathetic nervous system [19].…”
Section: Systemic Sialogoguesmentioning
confidence: 99%
See 2 more Smart Citations